Akurasi Model Zmijewski dan Grover dalam Memprediksi Financial Distress (Perusahaan Delisting pada BEI Tahun 2009-2018) - Maimunah, Maimunah; Kesuma, Ali (Keizai, 2020)
This research focuses on determining the suitable models for predicting financial distress in Indonesia. This research uses the Zmijewski model and the Grover model in predicting companies that have been delisted from Indonesia Stock Exchange. This research calculated the accuracy of each model which is the Zmijewski model and Grover model and then proved by hypothesis testing. The result of this research shows that the Zmijewski model and Grover model are not suitable for delisting companies in Indonesia, and the Grover model is no better than the Zmijewski model.